Localization and Performance of Auditory Brainstem Implants Based on MRI Measures of Paddle Placement - Cottrell, Justin; Breen, Matthew; Leeuwen, Matthew Van; Shapiro, William; Azadpour, Mahan; Friedmann, David; Jethanamest, Daniel; McMenomey, Sean; Pacione, Donato; Golfinos, John; Hagiwara, Mari; Moonis, Gul; Roland, J. Thomas, Jr. (Journal of Neurological Surgery Part B: Skull Base, 2025)
To develop and study a novel means of imaging auditory brainstem implant (ABI) paddle placement utilizing postoperative MRI images to determine correlation between ABI performance and ideal paddle placement properties.Single-center retrospective review and image analysis.Tertiary referral center.Patients >18 years old who received an ABI from 2009 to 2023 and had subsequent MRI and auditory performance testing completed.ABI paddle angulation and insertion depth measure, in addition to categories of auditory performance (CAP) score.Inclusion criteria were met by 21 patients with neurofibromatosis type 2 (NF2) who underwent ABI placement. The average insertional depth into the foramen of Luschka was 1.0 cm (Stdev 0.4), with average axial paddle angulation of 62.7 degrees (Stdev 29.7 degrees), average sagittal paddle angulation of 108.7 degrees (Stdev 44.4 degrees), and average coronal paddle angulation of −14.5 degrees (Stdev 62.4 degrees). Single variable linear regression showed a statistically significant negative relationship between insertion depth and CAP score (p = 0.049) once patients with large tumor burden were excluded. Insertion depth and axial angulation showed a negative correlation, in which higher insertion depth was associated with a decrease in axial angulation value, although not statistically significant.We present a novel means of measuring ABI paddle placement utilizing MRI to improve the objectivity of paddle placements assessments. Multicenter collaboration to increase the number of patients studied with this new measurement scheme will be required before stronger measurement associations can be determined.
Keywords: ABI paddle placement; ABI paddle localization; auditory brainstem implants; ABI performance; MRI; magnetic resonance imaging